A case of successful treatment of mucor pyelonephritis in a child with acute lymphoblastic leukemia (Indian Journal of Case Reports, 2018)
Invasive fungal infection (IFI) is a known complication in children with malignancy. Mucormycosis is a rare cause of IFI in children receiving chemotherapy. Isolated renal involvement of mucormycosis is extremely rare and carries a grave prognosis. A high index of suspicion and early management with antifungals and surgery is essential in the treatment of mucormycosis. Here, we describe a child with mucor pyelonephritis treated successfully with antifungals and surgery with the review of literature.